2001
DOI: 10.1111/j.1151-2916.2001.tb00805.x
|View full text |Cite
|
Sign up to set email alerts
|

Surprising Results of a Study on the Plasticity in Strontium Titanate

Abstract: Oxides such as SrTiO3 are expected to fail via brittle fracture at low temperatures. Surprisingly, in the present study, SrTiO3 single crystals could be plastically deformed in compression in two temperature ranges: from 78 K to ∼1050 K and from 1500 K to 1800 K. SrTiO3 was brittle at temperatures between these two ranges (∼1050–1500 K). This phenomenon of a ductile–brittle–ductile transition, together with microstructural investigations, suggests that the role of dislocations in the plasticity of ceramics mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
81
0
3

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(90 citation statements)
references
References 10 publications
6
81
0
3
Order By: Relevance
“…In the following, the pseudo-cubic setting will be referred by the subscript "c" while no indication will be given when the actual orthorhombic symmetry will be used. Transformations from cubic to orthorhombic (Pbnm) or orthorhombic to cubic directions are given by: (Doukhan & Doukhan 1986;Wright et al 1992, Besson et al 1996, BaTiO 3 (Doukhan & Doukhan 1986;Lin & Lu 2002), SrTiO 3 (Nishigaki et al 1991, Wang et al 1993, Mao & Knowles 1996, Matsunaga & Saka 2000Brunner et al 2001;Gumbsch et al 2001;Zhang et al 2002a, b;Jia et al 2005) { } c family.…”
Section: Structure and Possible Dislocationsmentioning
confidence: 99%
“…In the following, the pseudo-cubic setting will be referred by the subscript "c" while no indication will be given when the actual orthorhombic symmetry will be used. Transformations from cubic to orthorhombic (Pbnm) or orthorhombic to cubic directions are given by: (Doukhan & Doukhan 1986;Wright et al 1992, Besson et al 1996, BaTiO 3 (Doukhan & Doukhan 1986;Lin & Lu 2002), SrTiO 3 (Nishigaki et al 1991, Wang et al 1993, Mao & Knowles 1996, Matsunaga & Saka 2000Brunner et al 2001;Gumbsch et al 2001;Zhang et al 2002a, b;Jia et al 2005) { } c family.…”
Section: Structure and Possible Dislocationsmentioning
confidence: 99%
“…The mechanical properties of strontium titanate (SrTiO 3 ) crystals have received growing interest due to the fact that they can exhibit a large degree of plasticity even at low temperatures [3][4][5][6][7][8][9][10][11]. SrTiO 3 is an oxide with a cubic perovskite structure belonging to the Pm3m space group.…”
Section: Introductionmentioning
confidence: 99%
“…SrTiO 3 is an oxide with a cubic perovskite structure belonging to the Pm3m space group. It has been reported that SrTiO 3 crystals can plastically deform in temperature ranges from 78 K to 1050 K [3,4]. In addition, SrTiO 3 crystals can deform up to and over 10% if they deform at a slow strain rate of 10 −4 (s −1 ) [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…It is cubic except below 105 K where the crystal structure changes to tetragonal and below 65 K to orthorhombic (c/a = 1.002). Despite this seemingly simple structure the plastic behaviour (under compression) of this material recently turned out to exhibit quite a spectacular ductile-to-brittle-to-ductile transition (DBDT) [1,2] (see Fig.1). …”
Section: Introductionmentioning
confidence: 99%